Model of teaching translation in Chinese universities from the point of view of ecotranslatology (Eurasian Journal of Philology Science and Education, 2021)
Reforms in teaching translation in Chinese universities with a degree in Russian philology began in the 80s of the 20th century. As the reforms of teaching foreign languages in Chinese universities deepen, the methods of teaching translation in the specialty “philology of the Russian language” need to be improved. This article examines a new direction of translation theory, developed by the Chinese researcher Hu Gengshen, – eco-translatology, related to translation activity with the eco-environment. In this article, based on a deep analysis of the causes of existing problems in teaching translation in Chinese universities, we came to the conclusion: by applying the theory of eco-translation studies and its principles to the reform of translation training courses in Chinese universities, it is possible to form a three-part model, within which the teaching of students will include yourself three main aspects: knowledge of the language pair + ability to translate + general literacy; and the training of future specialists according to such a three-part ecological model will allow to solve many problems that are now facing higher education: to improve the quality of training in translation activities, to develop the ability to select and adapt in the eco-translation system and, finally, to increase the level of teaching professional translation from foreign languages.